RuRh Bimetallic Nanoparticles Stabilized by 15-membered Macrocycles-terminated Poly(propylene imine) Dendrimer: Preparation and Catalytic Hydrogenation of Nitrile—Butadiene Rubber - Wang, Yang; Peng, Xiaohong (Nano-Micro Letters, 2014)
A new fourth-generation poly(propylene imine) dendrimer (G4-M) containing 32 triolefinic 15-membered macrocycles on the surfaces has been synthesized. The bimetallic RuRh-dendrimer-stabilized nanoparticles (DSNs) were first prepared within G4-M by a co-complexation route. The new G4-M dendrimer has been characterized by 1H nuclear magnetic resonance, infrared radiation, and elemental analysis. The dendrimer-stabilized bimetallic ions and reduction courses were analyzed by UV-vis spectroscopy. High-resolution transmission electron microscopy and energy dispersive spectrometer were used to characterize the bimetallic nanoparticle size, size distribution, and particle morphology. The RuRh bimetallic DSNs showed high catalytic activity for the hydrogenation of nitrile-butadiene rubber.